2019
DOI: 10.11144/javeriana.rgsp18-36.ccmn
|View full text |Cite
|
Sign up to set email alerts
|

Calidad en la certificación de mortalidad y natalidad en un hospital universitario, Colombia año 2014

Abstract: El objetivo de este estudio fue describir y analizar el proceso de certificación de muerte y nacimiento de un hospital docente en Bogotá en el año 2014, tanto en términos de flujo de información como de calidad de la causa de muerte asignada. Se diseñó una metodología para monitorear la calidad y cobertura de las estadísticas de nacimientos y muertes hospitalarias. Durante su práctica de salud pública, diecisiete estudiantes de noveno semestre de Medicina participaron en la recopilación de información sobre 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Differences in cancer registry processes and follow-up practices have been assessed as being responsible for observed cancer survival differences [ 6 8 ]. Previous studies have reported the impact of incomplete registration and inclusion of death-certificated-only (DCO), death-certificate-notified (DCN), and death certificate-initiated (DCI) cases [ 6 , 9 11 ] and others on the impact of completeness of follow-up over cancer survival [ 7 , 8 , 12 15 ] employing real data from PBCR and hospital populations or simulations. However, the studies that evaluated impact of LFU on survival considered sample sizes over ≥1,000 cases, whereas PBCR in LMIC are usually regional with relatively small sizes (populations of around 300,000 to 1.5 million inhabitants, implying less than 500 cancer cases for individual cancer during a 5-year period) [ 16 ], and there is no information regarding the impact in such situations with few cases.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in cancer registry processes and follow-up practices have been assessed as being responsible for observed cancer survival differences [ 6 8 ]. Previous studies have reported the impact of incomplete registration and inclusion of death-certificated-only (DCO), death-certificate-notified (DCN), and death certificate-initiated (DCI) cases [ 6 , 9 11 ] and others on the impact of completeness of follow-up over cancer survival [ 7 , 8 , 12 15 ] employing real data from PBCR and hospital populations or simulations. However, the studies that evaluated impact of LFU on survival considered sample sizes over ≥1,000 cases, whereas PBCR in LMIC are usually regional with relatively small sizes (populations of around 300,000 to 1.5 million inhabitants, implying less than 500 cancer cases for individual cancer during a 5-year period) [ 16 ], and there is no information regarding the impact in such situations with few cases.…”
Section: Introductionmentioning
confidence: 99%